Bacillus thuringiensis Cry5B protein as a new pan-hookworm cure. Issue 2 (August 2018) - Hu, Yan; Nguyen, Thanh-Thanh; Lee, Alice.C.Y.; Urban, Joseph F.; Miller, Melanie M.; Zhan, Bin; Koch, David J.; Noon, Jason B.; Abraham, Ambily; Fujiwara, Ricardo Toshio; Bowman, Dwight D.; Ostroff, Gary R.; et al.
Abstract: Hookworms are intestinal nematode parasites that infect nearly half a billion people and are globally one of the most important contributors to iron-deficiency anemia. These parasites have significant impacts in developing children, pregnant women and working adults. Of all the soil-transmitted helminths or nematodes (STNs), hookworms are by far the most important, with disease burdens conservatively estimated at four million DALYs (Disability-Adjusted Life Years) and with productivity losses of up to US$139 billion annually. To date, mainly one drug, albendazole is used for hookworm therapy in mass drug administration, which has on average ∼80% cure rate that is lower (<40%) in some places. Given the massive numbers of people needing treatment, the threat of parasite resistance, and the inadequacy of current treatments, new and better cures against hookworms are urgently needed. Cry5B, a pore-forming protein produced by the soil bacterium Bacillus thuringiensis (Bt) has demonstrated good efficacy against Ancylostoma ceylanicum hookworm infections in hamsters. Here we broaden studies of Cry5B to include tests against infections of Ancylostoma caninum hookworms in dogs and against infections of the dominant human hookworm, Necator americanus, in hamsters. We show that Cry5B is highly effective against all hookworm parasites tested in all models. Neutralization of stomach acid improves Cry5B efficacy, which will aid in practical application of Cry5B significantly. Importantly, we also demonstrate that the anti-nematode therapeutic efficacy of Cry5B is independent of the host immune system and is not itself negated by repeated dosing. This study indicates that Bt Cry5B is a pan-hookworm anthelmintic with excellent properties for use in humans and other animals. Graphical abstract: Image 1 Highlights: Bacillus thuringiensis (Bt) Cry5B is a new pan-hookworm cure. Bt Cry5B is highly active against Ancylostoma caninum hookworm infections in dogs. Bt Cry5B is highly active against Necator americanus . Cry5B acts independent of the host immune system and directly on hookworms. Cry5B retains full bioactivity after repeated dosing.